Glosa do nienapisanej Historii Nowoczesnej Literatury Polskiej Aleksandra Wata - Łukaszuk, Małgorzata (Colloquia Litteraria, 2012)
Commentary on the unwritten history of modern Polish literature of Aleksander Wat The starting point for further consideration is for the author the intriguing convergence between the modern division of twentieth-century literature, proposed by Michał Paweł Markowski (for the “conservative” and “critical” modernism), and related to the same topic more than half century earlier Wat’s intuitions. In his Dziennik bez samogłosek [Diary without Vowels] (from January 1964) arguing with Milosz (who once teased Wat with a careless treatment of his work JA z jednej strony i JA z drugiej strony mego mopsożelaznego piecyka [Me from One Side and Me from the Other Side of My Pug Iron Stove]) draws an original story of Polish literature. Among important to Wat’s number of authors like Witkacy, Leśmian, Białoszewski and Różewicz, the author focuses on the last two, explaining why they occupy such a high place in Wat’s hierarchy. “Baka’s child” Białoszewski is dear to Wat because of the discoveries in the language area, and Różewicz on the other hand, although his presence in this statement may appear surprising, is for Wat a successor to the “full” stylistic secession. Another of the interesting to Wat writers – Gombrowicz, awakens in him ambivalent feelings from unrelenting criticism of a fellow writer (“complete ignorance”), to admiration of the Kosmos [Cosmos] (“Kosmos is a great book”).